The Investigation of Benzoic Acid Amounts in Some Foodstuffs Consumed in Ankara Region - Gülderen Güzel; Buket Er; Burak Demirhan; Gülderen Yentür; Aysel Bayhan Öktem (Journal of Pharmacy and Nutrition Sciences, 2013)
Benzoic acid and its salts are commonly used as a preservatives in food products. Excess amounts of benzoic acid can be harmful to human health. Therefore, the determination of benzoic acid is important in routine analysis of foods. The aim of this study was to determine amounts ofbenzoic acids in some foodstuffs and to evaluate whether these amounts were within the Turkish Food Codex (TFC) values or not. For this purpose, total number of 80 samples consisting of 20 ketchup (A, B firms), 20 sauce (C, D firms) and 40 jam samples (E, F, G, H, I, J, K firms) were collected from supermarkets, Ankara Region. In this research, spectrophotometric method was used for the quantitative determination of benzoic acid in ketchup, sauce and jam samples. Mean amounts (X± S.E) of benzoic acidin ketchupsamples of A and B firm were found as 152.32±18.41 and 1008.21±30.74 mg/kg, respectively. Mean amounts (X± S.E) of benzoic acidin sauce samples of C and D firm were determined as 990.85±26.00 and 1148.19±43.62 mg/kg, respectively. Also, mean amounts (X± S.E) of benzoic acidwere found as 435.27±26.07mg/kg in 8 jam samples of E firm. Our data revealed that while mean amounts of benzoic acid of A and C firms were found within TFC values, benzoic acid amounts of B and D firms samples were higher than the TFC values. Furthermore, some jam samples of firm E was not found appropriate to TFC.